Rancang Bangun Company Profile Berbasis Website dalam Upaya Peningkatan Aksesibilitas UMKM di Kota palopo - Stevani Boyo; Dasril; Mukramin (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to design and develop a website-based company profile as a promotional medium. The research method used in this study is the waterfall method. Data collection techniques include literature review, interviews, and observation. The design and construction of the website-based company profile for improving SME accessibility in Palopo City is designed using UML modeling language. The system is built using PHP programming language, Codeigniter Framework for data processing, HTML for website design, and MySQL database for data storage. The website-based company profile for improving SME accessibility in Palopo City is tested using Black Box testing, resulting in a well-functioning information system. Usability testing indicates that the system is suitable for use.